Antifouling behavior and separation performance of immobilized TiO2 in dual layer hollow fiber membranes - Dzinun, Hazlini; Othman, Mohd Hafiz Dzarfan; Ismail, Ahmad F.; Puteh, Mohd Hafiz; A. Rahman, Mukhlis; Jaafar, Juhana; Adrus, Nadia; Hashim, Nur Awanis (Wiley, 2017)
A set of titanium dioxide/polyvinylidene fluoride (TiO 2 /PVDF) dual layer hollow fiber (DLHF) membranes with various weight ratios (i.e., 0, 0.2. 0.5, 0.7, and 1) were prepared. This work investigated the effect of TiO 2 loading and ultraviolet (UV) irradiation intensity toward the separation performance using nonylphenol (NP) solution as the model sample. The study showed that TiO 2 nanoparticles were well distributed at the outer layer of DLHF membranes at lower concentration, but the particles were aggregated at higher concentration. The membrane with 0.2 TiO 2 /PVDF ratios showed uniform dispersion of TiO 2 and consequently recorded excellent NP solution flux. In the presence of UV light, the activation of super hydrophilicity properties of TiO 2 nanoparticles was improved and it was highly activated at higher energy, which results in the significant increase of NP solution flux. The results provide vital insights into the development of immobilized TiO 2 in DLHF membranes and applications in water treatment. POLYM. ENG. SCI., 58:1636–1643, 2018. © 2017 Society of Plastics Engineers.